PENGARUH PENERAPAN METODE PEMBELAJARAN ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JERMAN - Jamlean, Alexander Delvan; Maruanaya, Rita Fransina; Apituley, Patresia Silvana (Universitas Pattimura, 2025)
The purpose of this study was to determine the effect of the role-playing method on the speaking skills of students of the German Language Education programme, Faculty of Teacher Training and Education, Pattimura University, Ambon. The research method used was an experiment with a sample of 14 students, namely the first semester students of intake 2024 who took the course Productive Sprechfetigkeit 1. Data were collected using a testing technique in the form of a pre-test and a post-test. Before the post-test, the treatment was carried out, namely the implementation of learning using the role-playing method for 6 sessions. Based on the results of the hypothesis testing using the t-test, it can be seen that the use of the role-playing method has a significant effect on the students' speaking skills. The results of the calculation with the t-test showed that the t_count was greater than the t_table (1.980> 1.771). This proves that there is a significant difference between the pre-test and post-test scores. The t_count value which is greater than the t_table value also proves that the role play method has a positive effect on the students' speaking skills.